Features of Etiology of Community-Acquired Pneumonia Associated with COVID-19 - A. Yu. Popova; E. B. Ezhlova; Yu. V. Demina; A. K. Noskov; E. V. Kovalev; O. S. Chemisova; T. I. Tverdokhlebova; N. V. Pavlovich; S. O. Vodop’yanov; M. V. Tsimbalistova; N. E. Gaevskaya; S. V. Volovikova; et al. (Проблемы особо опасных инфекций, 2021)
Objective: comparative study of the etiological structure of community-acquired pneumonia in SARSCoV-2 “+”and SARS-CoV-2 “-“ patients who sought help from medical organizations in the Rostov Region.Materials and methods. Biological material from 508 patients diagnosed with community-acquired pneumonia who were on outpatient treatment or in hospitals in Rostov-on-Don was studied. Verification of respiratory viruses, including SARS-CoV-2 RNA, as well as M. pneumoniae, C. pneumoniae, and L. pneumophila was performed by polymerase chain reaction in nasopharyngeal smears. Bacteriological analysis of sputum was carried out using differential diagnostic media, identification of isolated pathogens was carried out using time-of-flight mass spectrometry on Autoflex (Bruker Daltonics) with BioTyper 3.0 software.Results and discussion. During the spread of a new coronavirus infection in the Rostov Region, the main etiological agent of community-acquired pneumonia is the new SARS-CoV-2 coronavirus. Specific character of pneumonia in patients with laboratory-confirmed COVID-19 is a higher incidence of mixed infection of both viral and bacterial etiology. Against the background of detection of a new coronavirus infection in patients with pneumonia, cases of detection of other types of coronaviruses have been registered (HKU-1,OC43, HL-63 and 229Е). The most common etiological agent of bacterial pneumonia in patients was Streptococcus spp., both in patients with COVID-19-associated pneumonia and in patients who tested negative for SARS-CoV-2. Coronavirus patients represent a high risk group for the development of mycotic lung lesions.